2007
DOI: 10.1007/s10201-006-0197-6
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of predation of three aquatic heteropteran bugs on Culex quinquefasciatus larvae

Abstract: The aquatic bugs Anisops bouvieri Kirkaldy 1704 (Heteroptera: Notonectidae), Diplonychus (=Sphaerode-ma) rusticus Fabricius 1781, and Diplonychus annulatus Fabricius 1781 (Heteroptera: Belostomatidae) are common members of the freshwater insect communities of the East Calcutta Wetlands along the eastern fringe of Kolkata, India. These insects are established predators of dipteran larvae and other organisms. A comparative account of their predatory effi ciency was made using larvae of Culex quinquefasciatus Say… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 28 publications
4
28
1
Order By: Relevance
“…arabiensis DNA (Table 1). Although it has been suggested that Belostomatidae are important mosquito predators (Saha et al 2007, 2010), this family was found to have the lowest positive rates of the Hemiptera included in our study. A previous serological study (Service 1977) also showed that the positive rate in Belostomatidae (genus Sphaerodema ) was lower than for other Hemipteran species.…”
Section: Discussioncontrasting
confidence: 80%
“…arabiensis DNA (Table 1). Although it has been suggested that Belostomatidae are important mosquito predators (Saha et al 2007, 2010), this family was found to have the lowest positive rates of the Hemiptera included in our study. A previous serological study (Service 1977) also showed that the positive rate in Belostomatidae (genus Sphaerodema ) was lower than for other Hemipteran species.…”
Section: Discussioncontrasting
confidence: 80%
“…Both herbivorous (most Corixidae) and carnivorous (Notonectidae, Belostomatidae, Nepidae, Pleidae), these bugs have considerable influence on aquatic food webs, feeding on zooplankton, insects, and small vertebrates, and serving as prey for large insects and fish (e.g., Murdoch et al, 1984;Hickley et al, 1994;Blaustein, 1998;Gilbert & Burns, 1999;Hampton et al, 2000). Additionally, the economic importance of at least three of these families as biological control agents of disease-carrying mosquitos is well established (Nam et al, 2000;Saha et al, 2007, reviewed in Papacek, 2001. Notonectids, in particular, have been shown to prey preferentially on mosquito larvae, drive mosquitoes to local extinction (Murdoch et al, 1984), and even deter oviposition behavior in gravid mosquitoes, including Anopheles gambiae, the primary vector of human malaria (Blaustein et al, 2005;Munga et al, 2006).…”
Section: )mentioning
confidence: 97%
“…arabiensis DNA (Table 1). Although it has been suggested that Belostomatidae are important mosquito predators (Saha et al 2007(Saha et al , 2010, this family was found to have the lowest positive rates of the Hemiptera included in our study. A previous serological study (Service 1977) also showed that the positive rate in Belostomatidae (genus Sphaerodema) was lower than for other Hemipteran species.…”
Section: Discussionmentioning
confidence: 53%